2013
DOI: 10.5194/sed-5-883-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grassland fire effect on soil organic carbon reservoirs in semiarid environment

Abstract: Abstract. The aim of this work was to investigate the effect of a experimental fire, used for grassland management, on soil organic carbon (SOC) reservoirs. The study was carried out on Hyparrhenia hirta (L.) Stapf (Hh) grassland and Ampelodesmos mauritanicus (Desf.) T. Durand and Schinz (Am) grasslands, located in the north of Sicily. Soil samples were collected at 0–5 cm before and after experimental fire and SOC was measured. During grassland fire soil surface temperature was monitored. Biomass of both gras… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
2
5
0
1
Order By: Relevance
“…It also aids in regulating soil temperature and provides habitat and substrates for soil biota. Furthermore, it can be a major source of readily mineralizable nutrients (Neary et al, 1999) and therefore supplies the plants with most of the available P and S, and virtually all of the available N. Soil OM's role in N storage is especially important in forests because their continued high productivity depends, to a large extent, on large supplies of available N. In contrast, Novara et al (2013) showed that there was no significant difference between burned and unburned sites as far as OM was concerned.…”
Section: Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It also aids in regulating soil temperature and provides habitat and substrates for soil biota. Furthermore, it can be a major source of readily mineralizable nutrients (Neary et al, 1999) and therefore supplies the plants with most of the available P and S, and virtually all of the available N. Soil OM's role in N storage is especially important in forests because their continued high productivity depends, to a large extent, on large supplies of available N. In contrast, Novara et al (2013) showed that there was no significant difference between burned and unburned sites as far as OM was concerned.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…Fire is an important abiotic factor that causes substantial changes to the soil profile and characteristics depending on the severity and the duration of burning (Amaranthus, 1989). The most affected soil properties are texture (Scharenbroch et al, 2012;Norouzi and Ramezanpour, 2013), organic matter (OM) content (Novara et al, 2013), nutrient availability (Scharenbroch et al, 2012), porosity, pH (Certini, 2005;León et al, 2013), and electrical conductivity (EC) (León et al, 2013;Norouzi and Ramezanpour, 2013). Fire leads to burning of OM and this in turn affects the nutrient status of soil (Hart et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cotejando-se os dados é evidente que os referidos municípios são contribuintes potenciais para a poluição do meio ambiente devido a prática da queima e as consequências provenientes dela naquela região. A queima reduz o estoque de carbono orgânico do solo (NOVARA, et al, 2013). No entanto, se faz necessário o manejo dos campos de pastagens para que não sejam substituídos por vegetação lenhosa.…”
Section: Discussão E Resultadosunclassified
“…A lot of attention is paid to the problem of postpyrogenic soil change, its properties, soil regime, and functions in a boreal zone. A variety of research studies are devoted to pyrogenic transformation of the water regime, vegetation, and forest landscapes in whole [6][7][8][9][10][11][12][13][14][15]. However, data on similar studies of the pyrogenic transformation in polar, tundra, and subboreal landscapes of cryolithozone are extremely rare in the literature.…”
Section: Introductionmentioning
confidence: 99%